A S7-1200 PLC-BASED MOTION SEAT SYSTEM FOR 3D CINEMA APPLICATIONS - Ho, Thanh-Phuong; Dieu, Nghia; Tran, Quang-Huy; Nguyen, Thi-Ngoc-Thao; Le, Thi-Hong-Lam; Nguyen, Phong-Luu; Nguyen, Hai-Thanh; Pham, Gia-Loc; Nguyen, Ha-Thien-Phuc; Tran, Van-Toan; Nguyen, Truong-Viet; Pham, Ngoc-Bao; Nguyen, Van-Bac; Hoang, Minh-Giap (Asosiasi Peneliti Sriwijaya, 2026)
Immersive cinematic experiences are becoming increasingly important in enhancing audience satisfaction. By integrating various pneumatic and electrical actuators, a 3D cinema seat system is developed to simulate real-time motion effects such as vibration, lifting, wind blowing, and mist spraying. These effects are synchronized with movie content to improve viewer engagement. In this paper, we present a prototype that utilizes a Siemens S7-1200 PLC as the main controller and a Weinview HMI for interaction. The system's effects are triggered through a scenario-based timeline controlled via ladder logic. Through experimental trials, the model demonstrates high responsiveness and reliability, meeting real-time synchronization requirements. A supervision interface is also designed to allow users to manage effect sequences during playback.